2017
DOI: 10.7554/elife.30860
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution mRNA expression time course of embryonic development in zebrafish

Abstract: We have produced an mRNA expression time course of zebrafish development across 18 time points from 1 cell to 5 days post-fertilisation sampling individual and pools of embryos. Using poly(A) pulldown stranded RNA-seq and a 3′ end transcript counting method we characterise temporal expression profiles of 23,642 genes. We identify temporal and functional transcript co-variance that associates 5024 unnamed genes with distinct developmental time points. Specifically, a class of over 100 previously uncharacterised… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
361
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(425 citation statements)
references
References 100 publications
37
361
5
Order By: Relevance
“…The morphological and developmental processes of zebrafish embryos at different stages as described byKimmel et al (1995) and the period of exposure to high ambient temperatures used in this study are illustrated inFigure 1c. In this study, a distinct reduction in survival ability was observed after treatment at 24 hpf in the pharyngula period (Prim-5,White et al, 2017), compared to the survived eggs at the pre-treatment (5 hpf) stage in both experimental groups, with a significant (p < 0.0002) lower survival ability in temperature-treated group (73.30% ± 0.58% in control vs. 70.19% ± 0.57% in treated groups). This stage of devel-…”
mentioning
confidence: 58%
“…The morphological and developmental processes of zebrafish embryos at different stages as described byKimmel et al (1995) and the period of exposure to high ambient temperatures used in this study are illustrated inFigure 1c. In this study, a distinct reduction in survival ability was observed after treatment at 24 hpf in the pharyngula period (Prim-5,White et al, 2017), compared to the survived eggs at the pre-treatment (5 hpf) stage in both experimental groups, with a significant (p < 0.0002) lower survival ability in temperature-treated group (73.30% ± 0.58% in control vs. 70.19% ± 0.57% in treated groups). This stage of devel-…”
mentioning
confidence: 58%
“…Moreover, chromatin accessibility increases during the stages preceding transcription activation (Figure 3a). As a control, we selected promoters of genes that are not expressed until two days post fertilization [16]. At these promoters, chromatin accessibility is extremely low and does not change from 256-cell to 80% epiboly.…”
Section: Chromatin Accessibility At Regulatory Elements Precedes Tranmentioning
confidence: 99%
“…The accessibility of promoters and enhancers prior to gene activation, as well as the increase in accessibility prior to transcription activation, are easily visible at specific gene loci. For example, the promoter and putative enhancer of gata6, a gene that is activated at dome stage [16,35], are accessible at 256cell stage and their accessibility increases prior to transcription ( Figure 3c). A similar relationship between accessibility and transcription activation can be observed for the regulatory elements of olig4 (activated at shield stage), and the experimentally validated enhancers of neurog (activated at 80% epiboly stage), ta (activated at sphere stage), and otx2 (activated at 80% epiboly stage) [36][37][38] (Figure 3c, Figure S5).…”
Section: Chromatin Accessibility At Regulatory Elements Precedes Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not late replicating until the end of gastrulation or bud stage (10 hpf) (Siefert et al, 2017). Previous work in zebrafish has found ZnF proteins on chromosome 4 to undergo robust expression from the initiation of zygotic transcription until mid-gastrula stage (White et al, 2017). Since many chromosome 4 genes are downregulated across ethanol-treated individuals during gastrulation, ethanol may interfere with replication timing, blocking the early-to-late replication switch, or chromatin remodeling.…”
Section: Discussionmentioning
confidence: 99%